Relevansi Pendidikan Anak dalam Islam Perspektif Abdullah Nashih ‘Ulwan dan Kurikulum Merdeka di Sekolah Dasar - Zulfa, Athena; Zuhriyah, Amifatuz (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Abdullah Nashih ‘Ulwan presents views on educating children in Islam based on the teachings of Prophet Muhammad (PBUH) in the book "Tarbiyatul Aulad fil Islam". This book has been translated into various languages and serves as a reference for Islamic child education worldwide, including in Indonesia. The seven points mentioned in the book are faith, morals, physical education, intellect, spiritual education, social education, and sex education. The "kurikulum merdeka" or independent curriculum is the latest curriculum implemented since 2022. The curriculum change started from first grade and fourth grade and has been ongoing for two years, prompting researchers to focus on studying student textbooks in the fourth grade. This study aims to analyze the perspective of Abdullah Nashih Ulwan with the Islamic Religious Education and Character Education books used in Elementary Schools. This research is qualitative in nature, specifically library research, and the gathered data are analyzed using text and language analysis methods, namely content analysis. The results of this research show that there is relevance in the compilation of Islamic religious education and character education books for fourth grade in the independent curriculum, presented in ten chapters with six points previously proposed by Abdullah Nashih ‘Ulwan, while physical education is provided in a separate subject, namely physical education, sports, and health.